Study on the Coupling Coordination and Driving Factors of Provincial Digital Economy and High Quality Development of Tourism Industry - Xie, Yanhui (Transactions on Economics, Business and Management Research, 2024)
With the rapid progress of information technology, unprecedented changes have been brought to various industries. As an important component of the national economy, the tourism industry has become increasingly closely coupled and coordinated with the digital economy in its development. This article aims to analyze the coupling and coordination relationship between the provincial digital economy and the high-quality development of the tourism industry, reveal the inherent correlation and interaction mechanism between the two, and explore the key factors that affect the degree of coupling and coordination, providing reference suggestions for policy makers to promote the high-quality development of the tourism industry.